Evaluasi Evaluasi Keseuaian Lahan, Adaftasi dan Penebaran Benih pada Produksi Ikan Nila (Oreochromis niloticus) di Tambak Desa Coppotompong, Kecamatan Mandalle Kabupaten Pangkajene Kepulauan. - Rifai, Ratnawati; Sani, Asrianti; Nurdin, Fauziah (Unit Penelitian dan Pengabdian Masyarakat Politeknik Pertanian Negeri Pangkajene Kepulauan, 2025)
Tilapia seeds are one of the main factors determining the success of tilapia cultivation, so the use of quality (superior) seeds is very important to produce high productivity so that it can provide greater benefits for farmers. Community service activities aim to educate farmers about the importance of recognizing good tilapia seeds and acclimatizing seeds for enlargement in ponds. Community Service was carried out from April to September 2024 at the tilapia fish pond unit in Coppotompong Village, Mandalle District, Pangkep Regency. The implementation procedure for community service begins with a location survey at the pond, counseling/lectures, and assistance to farmers. The performance of good tilapia seeds for maintenance in ponds must be healthy (no wounds, intact fins, not dull in color, active movement), uniform seed size, and the number of vertebrae ranging from 44-45. Seeds must be acclimatized before being stocked and the stocking density depends on the carrying capacity of the pond.